2023
DOI: 10.1177/02692155231185446
|View full text |Cite
|
Sign up to set email alerts
|

Physical functioning factors predicting a return home after stroke rehabilitation: A systematic review and meta-analysis

Abstract: Objectives This systematic review and meta-analysis sought to identify the physical functioning factors associated with home discharge after inpatient stroke rehabilitation. Data sources A search of PubMed, Embase, CINHAL, The Cochrane Library (Trials), Web of Science, and PEDro were conducted up until May 2023. Methods Two independent reviewers selected studies for population (patients with stroke), predictive factors (physical functioning), outcome (discharge destination), setting (inpatient rehabilitation),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Many studies have shown that ADL on admission and discharge were predictors of discharge destination of stroke patients [ 9 , 19 , 20 ]. The discharge destination predictors have been reported for several diseases, including spinal cord injury and post-proximal femoral fracture [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that ADL on admission and discharge were predictors of discharge destination of stroke patients [ 9 , 19 , 20 ]. The discharge destination predictors have been reported for several diseases, including spinal cord injury and post-proximal femoral fracture [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, home-based supportive care improves the social and emotional QOL of patients with advanced cancer [ 8 ]. In stroke patients, a systematic review and meta-analysis reported that higher independence in ADLs on admission predicted a return to home [ 9 ]. Regarding cancer patients, performance status, age [ 10 ], and frailty [ 11 ] have been reported as factors associated with discharge home, but no definite conclusion has been reached.…”
Section: Introductionmentioning
confidence: 99%
“…Physical therapists who were trained to perform standardized assessment procedures conducted all measurements in this study. The primary outcome of e cacy was the Berg Balance Scale (BBS) score [25,26]; the secondary outcome was the Functional Ambulation Category (FAC)…”
Section: Assessmentmentioning
confidence: 99%
“…Typically, stroke survivors have hemiplegia and/or cognitive impairments that negatively affect functional independence in activities of daily living (ADL) 2 ) . Rehabilitation is often prescribed to these patients to recover functional independence 3 , 4 ) . One of the goals of stroke rehabilitation is home discharge 5 ) .…”
Section: Introductionmentioning
confidence: 99%